2019
DOI: 10.1111/1365-2435.13352
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the toolbox of nutrient limitation studies: A novel method of soil microbial in‐growth bags to evaluate nutrient demands in tropical forests

Abstract: Ecosystem processes and the organisms involved are generally limited by the availability of one or more elements in soil, an important phenomenon to consider for our understanding of ecosystem functioning and future changes. Especially in tropical forests, typically growing on nutrient depleted soils, nitrogen (N), phosphorus (P) or other limitations are assumed. However, large‐scale nutrient manipulation experiments revealed complex site‐specific patterns and several authors raised the need for novel approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 119 publications
0
2
0
1
Order By: Relevance
“…However, under conditions of low N, microbes stimulate the release of N through accelerating decomposition of organic matter (Dijkstra et al, 2013). Besides, it is also likely that the absence of fertiliser caused nutrient demand that prompted increased soil microbial activity to supply/bridge the limiting nutrient (Camenzind et al, 2019), perhaps explaining the more N mineralised in the no input control than the fertilised systems.…”
Section: Discussionmentioning
confidence: 99%
“…However, under conditions of low N, microbes stimulate the release of N through accelerating decomposition of organic matter (Dijkstra et al, 2013). Besides, it is also likely that the absence of fertiliser caused nutrient demand that prompted increased soil microbial activity to supply/bridge the limiting nutrient (Camenzind et al, 2019), perhaps explaining the more N mineralised in the no input control than the fertilised systems.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, carbon-acquiring enzymes showed greater variation compared to nitrogen-acquiring enzymes from the second to third growth periods ( Supplementary Table 7 ). Meanwhile, the lower SOC content of early- and mid- species in the third growth period may increase the microbial carbon limitation ( Supplementary Figure 5 ; Camenzind et al, 2019 ). However, in late species, the SOC content increased in the third growth period, whereas the soil enzyme activity decreased, possibly because changes in SOC lag behind those of soil microorganisms and thus increase the sensitivity of the soil microbial response to soil nutrients during PSF, particularly in late- species ( Bever et al, 1997 ; Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…En altitudes de 1000 m, 2000 m y 3000 m, en suelos fertilizados con N y P, se obtuvo aumento significativo de hongos por la influencia del P (Camenzind et al, 2015;Camenzind, Scheu y Rillig, 2019); a mayores altitudes, el P aumentó el tamaño de las hifas; comportamiento contrario ocasionó el N (Camenzind et al, 2019). Por otro lado, cuando al suelo se fertiliza con N, P, K y Na, en altitudes de 194 m, 210 m y 3025 m, se obtuvo aumento de hongos en restos de celulosa, por la adición de N, lo que sugiere que la principal limitante para degradación de la celulosa es la falta de N en el suelo (Nottingham et al, 2018).…”
Section: Hongos Bacterias Y Archaeas En El Suelounclassified